Allosteric modulators of cannabinoid receptor 1: developing compounds for improved specificity - Dopart, Rachel (Drug Metab Rev, 2018)
The cannabinoid receptor 1 (CB(1)) is a G protein-coupled receptor (GPCR) that is located primarily in the central nervous system. CB(1) is a therapeutic target which may impact pathways to mediate pain, neurodegenerative disorders, hunger, and drug-seeking behavior. Despite these benefits, development of orthosteric therapeutic compounds, which target the endogenous ligand-binding site of CB(1,) has been challenging due to detrimental side effects including psychoactivity, depression, and suicidal thoughts. However, CB(1) also has an allosteric binding site(s), which is topographically distinct from the orthosteric site. Allosteric modulation of CB(1) has a number of potential advantages including providing a mechanism for more precise control of downstream pathways and circumventing these side effects. In this review, we summarize the concept of allosteric modulation and focus on the structure activity relationship studies of the well-characterized allosteric modulators, ORG27569 and PSNCBAM-1 and their derivatives, and a few other recent modulators. We review studies on the properties of these modulators on CB(1) signaling in cells and their effects in vivo. While many current allosteric modulators also produce complex outcomes, they provide new advances for the design of CB(1) centered therapeutics.